Leading global diversity, equity, and inclusion : a guide for systemic change in multinational organizations - Anand, Rohini (Oakland Berrett-Koehler publishers, 2022)
"This book offers five proven principles so multinational companies can advance diversity, equity, and inclusion with a nuanced understanding of local contexts across countries and cultures. It's easy to fall into the trap of using a single-culture worldview when implementing global DEI in organizations. But what makes DEI change efforts successful in one country may have opposite, unintended consequences in another. How do companies find the right balance between anchoring their efforts locally while pushing for change that may disrupt existing power dynamics? This is the question at the heart of global DEI work. Along with practical advice and examples, Rohini Anand offers five overarching principles derived from her own experience leading global DEI transformation and interviews with more than sixty-five leaders to provide a through line for leading global DEI transformation in divergent cultures: Local relevance-understanding markets and acknowledging local beliefs, regulations, and history-is essential for global success. This groundbreaking book explicitly details how to take local histories, laws, and practices into account in DEI transformation work while promoting social justice worldwide"--
Includes bibliographical references (pages 229-250) and index.
Keywords: Diversity in the workplace; International business enterprises -- Personnel management; Organizational change; Multiculturalism